1993
DOI: 10.1007/bf00043936
|View full text |Cite
|
Sign up to set email alerts
|

Embryogeny of gymnosperms: advances in synthetic seed technology of conifers

Abstract: Synthetic seed technology requires the inexpensive production of large numbers of high-quality somatic embryos. Proliferating embryogenic cultures from conifers consist of immature embryos, which undergo synchronous maturation in the presence of abscisic acid and elevated osmoticum. Improvements in conifer somatic embryo quality have been achieved by identifying the conditions in vitro that resemble the conditions during in ovulo development of zygotic embryos. One normal aspect of zygotic embryo development f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
131
1
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 296 publications
(136 citation statements)
references
References 184 publications
(153 reference statements)
3
131
1
1
Order By: Relevance
“…Somatic embryos appear to undergo a decreasing sensitivity to ABA during maturation. The same observation has also been documented in conifers (Attree and Fowke 1993). In alfalfa and Brassica napus tissue culture-derived embryos desiccation tolerance can be induced with ABA only at a specific stage in their development (McKersie et al 1989;Brown et al 1993).…”
Section: Resultssupporting
confidence: 71%
“…Somatic embryos appear to undergo a decreasing sensitivity to ABA during maturation. The same observation has also been documented in conifers (Attree and Fowke 1993). In alfalfa and Brassica napus tissue culture-derived embryos desiccation tolerance can be induced with ABA only at a specific stage in their development (McKersie et al 1989;Brown et al 1993).…”
Section: Resultssupporting
confidence: 71%
“…For A. angustifolia, this is a critical point since this species has undergone continuous declines in the extent of its occurrence. Genotype specificity for embryogenic initiation occurs in conifers (Attree & Fowke, 1993). In our experiments, differences was observed between genotypes tested up to 10.6% in the induction rate.…”
Section: Discussionmentioning
confidence: 43%
“…These include influence of the genotype, effect of the stage of development, and induction potential of the culture medium (Radojevic et al, 1999), particulary of sucrose, nitrogen level and composition, mineral elements, agar, plant growth regulators, and pH (Tautorus et al, 1991). The maturation of conifer somatic embryos occurs in the presence of abscisic acid (ABA) and an osmotic agent (Attree & Fowke, 1993). ABA inhibits cleavage polyembryony, thus allowing embryo singulation, further development, and maturation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The key aspects of quality considered are the ability to survive desiccation and the ability to germinate vigorously. The importance of both abscisic acid (ABA) and water stress in increasing embryo yield and promoting embryo development have been described previously [2,3]. This work demonstrated that raising both ABA and water stress are beneficial to embryo quality, as they prevent precocious germination and promote full morphological development and accumulation of storage reserves.…”
Section: Improvements In Embryo Performance and Germinationmentioning
confidence: 74%